Asymptomatic Nonunion Scaphoid Fracture After Kirschner Wire Fixation of Trans-Scaphoid Lunate Dislocation: A Case Report with 3 Years of Follow-up - Huwae, Thomas Erwin Christian Junus; Dradjat, Respati Suryanto; Refa, Adytia Andreyta (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Trans-scaphoid lunate dislocation is an orthopaedic injury, mostly because of high energy trauma. Due to subtle clinical and radiological findings, it might be easily left undiagnosed, with estimated 25% cases are missed at initial assessment in emergency department. Non-union scaphoid, which accounts for 5-10% of all scaphoid fractures treated with K-wires fixation, mostly occurs in young and active individual. Case Presentation: Thirty-seven-years-old right-handed man complained pain, and restricted range of motion (ROM) on his right wrist after fell from 2m height. Loss of symmetry and parallelism of joint space in Gilula's line shown in X-ray, possible for a trans-scaphoid lunate dislocation. We performed dorsal approach and internal fixation using Kirschner wire (1.0). The patient had a short arm cast for 4 weeks. The K-wires were removed 5 weeks postoperatively. We achieved good result clinically in 3, 9, and 36 months of follow up (Mayo Wrist Score of 70, 80, 90, respectively). The ROM of wrist is preferable than pre-surgery (RD 20o, UD 20o, and WF-WE 60o) with avascular necrosis of scaphoid in 9th month follow up (in 2019). Unfortunately, at 3 years of follow up, X-ray showed non-union scaphoid, avascular necrosis, and osteophytes between scaphoid and radius. Discussion: Unless it is asymptomatic, surgery is the recommended treatment for scaphoid non-union in order to limit further morbidity from pain, weakness, and stiffness of the wrist joint. However, in this case, the patient has been doing any activities with his right hand normally and never felt any pain in the last 2 years, eventhough the X-ray shows fracture line at distal of scaphoid. Thus, we choose not to do any treatment for it. Conclusion: In the case of trans-scaphoid lunate dislocation, the use of K-wire fixation shows excellent clinical outcome, but radiological finding shows non-union scaphoid with osteophytes, thus it has possibility to develop degenerative disease in the future. Keywords: Trans-scaphoid Lunate dislocation; Non-union; K-wire Fixation